2011
DOI: 10.2166/wst.2011.460
|View full text |Cite
|
Sign up to set email alerts
|

Sources and leaching of manganese and iron in the Saigon River Basin, Vietnam

Abstract: High concentrations of manganese and iron in the Saigon River are major problems for the water supply in Ho Chi Minh City (HCMC), Viet Nam. To identify their sources and leaching processes, we surveyed water quality along the Saigon River and ran batch leaching tests using soil and sediment samples. Two important leaching processes were identified: acidic leaching from acid sulfate soil (ASS) in the middle reaches of the river, and Mn dissolution and Fe reduction from sediments in the downstream reaches. Low p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This is supported by Hulten et al [54] who reported that sediment is the main source of Mn, specifically on the surface of the sediment particles. Moreover, wastewater discharged from the metal industry flows into the river, lowering its pH and facilitating the sediment dissolution into the river [55]. Hence, concentrated Mn in river and sediment contributes to high Mn level in C. fluminea .…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by Hulten et al [54] who reported that sediment is the main source of Mn, specifically on the surface of the sediment particles. Moreover, wastewater discharged from the metal industry flows into the river, lowering its pH and facilitating the sediment dissolution into the river [55]. Hence, concentrated Mn in river and sediment contributes to high Mn level in C. fluminea .…”
Section: Resultsmentioning
confidence: 99%
“…For example, acid sulfate soil (ASS) is widely distributed in tropical regions and is stable under anoxic conditions. However, when ASS is exposed to oxygen (atmosphere) with water, which is often driven by logging during a rainy season, ASS starts to be oxidized, producing H + and causing severe acidification of the downstream rivers (Sammut et al 1996;Vuai et al 2003;Van Ha et al 2011). In the Kahayan River in Central Kalimantan, Indonesia, the surface water pH dropped to as low as 3 due to ASS during a rainy season (Haraguchi 2007).…”
Section: Loggingmentioning
confidence: 99%
“…S2F). The acidic water upstream of the Sai Gon River was assigned to the interactions with acid sulphate soils within its watershed (Nguyen et al, 2011;Strady et al, 2017). Despite a mesotrophic status in the Saigon river compared to an oligotrophic one in the Dong Nai (Nguyen et al, 2019b), the POC in both river systems was mainly associated with allochthonous organic matter, e.g., from untreated wastewater, rather than the autochthonous phytoplankton.…”
Section: Seasonal Variations In Ree Geochemistrymentioning
confidence: 99%